Pengembangan E-Learning dalam Memberikan Pelayanan terhadap Siswa di MTs Negeri 4 Gunugkidul pada Masa Pandemi Covid-19 - Isfi Muzari (Jurnal Pendidikan Madrasah, 2022)
This research aims to find out the development of e-learning in serving students during the distance learning process. This research uses exploration case study methods with a qualitative approach used to obtain information on constraints and solutions due to the Covid-19 pandemic to the development of e-learning. The results showed that there were several e-learning developments carried out at MTs Negeri 4 Gunungkidul, including hosting to store madrasah website data and domain rental as a website address so that it could be accessed through the internet, as well as training tutorials for teachers and students. This is to bridge the obstacles experienced by teachers and students in the use of e-learning, namely servers that are down and difficult to access and lack of communication and socialization between students and teachers. In addition, the use of e-learning can make it easier to update teaching materials and task checks.